Intramedullary nailing for calcaneal fractures: what are the available techniques? A review of the literature - Rosati Tarulli, Filippo; Izzo, Antonio; Coviello, Antonio; Smeraglia, Francesco; Balato, Giovanni; Mariconda, Massimo; Bernasconi, Alessio (Lo Scalpello - Journal, 2022)
Objective. Displaced intra-articular fractures of the calcaneus (DIACF) may be treated in several ways. In recent years, intramedullary locking devices (ILD) have been proposed with the aim to reduce complications and improve long-term results. In this regard, we have reviewed the literature in order to identify devices currently available and evaluate their characteristics. Methods. Following a PRISMA checklist, Medline, Scopus and EMBASE databases were searched to identify studies reporting use of ILDs to treat DIACFs. In this review, only technical notes were included. Manuscripts selected were critically analysed in order to highlight common points and differences among surgical techniques. Results. Overall, four technical notes dealing with ILDs were found, of which two concerned the Calcanail® (FH Orthopedics, Heimsbrunn, France) and two the C-Nail® implant (Medin, Nov. Město n. Moravě, Czech Republic). While the Calcanail® is stabilised by two screws and allows indirect reduction of the posterior facet, the C-Nail® involves direct visualisation of the joint space and use of multiple multi-directional screws to achieve final stabilisation. Conclusions. Although similar in the design, the Calcanail® and the C-Nail® lead to the reduction and stabilisation of fragments through different mechanisms. In both cases the restoration of heel height and anatomical reduction of the subtalar joint are the primary goals of surgery.